2017
DOI: 10.7860/jcdr/2017/22817.9558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Masood’s and Modified Masood’s Scoring Systems in the Cytological Diagnosis of Palpable Breast Lump Aspirates

Abstract: Introduction: Fine Needle Aspiration Cytology (FNAC) has a leading role in the assessment of breast lesions. Masood's Scoring Index (MSI) and its modification (Modified Masood's scoring index; MMSI) has been proposed to aid in sub-grouping breast lesions and to help in subsequent management. Aim:To assess and compare the diagnostic accuracy of MSI and MMSI by subsequent correlation with histopathology. Materials and Methods:The study was cross-sectional in nature and was conducted in a tertiary care setting. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
2
1
Order By: Relevance
“…The concordance rate of MMSI (93.9%) over MSI (88.7%) was found to be statistically significant for all cytological categories. These findings are similar to those of Cherath and Chithrabhanu [10] and of Nandini et al [4]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The concordance rate of MMSI (93.9%) over MSI (88.7%) was found to be statistically significant for all cytological categories. These findings are similar to those of Cherath and Chithrabhanu [10] and of Nandini et al [4]. …”
Section: Discussionsupporting
confidence: 82%
“…We observed a sensitivity and specificity of 95 and 100%, respectively, which was similar to Cherath and Chithrabhanu [10]; however, Masood et al [5] found a sensitivity of 85%. Diagnostic accuracy in our study was reported to be 98.3%, which is comparable to that reported by other authors (96–97.5%) [5, 10]. …”
Section: Discussionsupporting
confidence: 52%
“…Thus, a diagnostic accuracy of 84.6% was seen in this category. This is slightly less than the accuracy found in studies by Nandini et al [8] and Cherath et al [19]. This disparity can be accounted for due to the smaller sample size in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…In category 2, nine discordant cases were observed, out of which 7 were cases of PBD with atypia, while the other 2 were cases of low-grade IDC. These cases represent the grey zone cases of cytology and are prone to potential pitfall [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Irshad et al[16] presented a survey on different feature extraction methods available for the histopathological image. Recently, Rekha et al and Cherath et al[44,45] proposed a modified scoring system for breast cancer grading. Authors in their research works have suggested six morphological features like cellular pleomorphism, cellular arrangement, myoepithelial cells, anisonucleosis, nucleoli, and chromatin clumping.…”
mentioning
confidence: 99%